One hundred and two conspicuous birds across an elevation gradient in the western Andes of central Peru - Castañeda, Elena; Facultad de Ciencias Biológicas, Universidad Nacional Mayor de San Marcos (2023)
Birds are the most diverse group of vertebrates, who through flight can move small to longdistances, however their distributions can be constrained by environmental variables such astemperature and precipitation which change with altitude in the Andes. The objective of the studywas to determine the richness and abundance of birds for vegetation types across an altitudegradient. Bird species and abundance were measured using point counts and by total counting,supplemented by opportunistic records, surveys were conducted in October 2015. We recorded 102conspicuous bird species of which eight are endemic species reported for Peru. The greatest richnessof bird species was between 2,000 and 3,000 m, but there were differences in the distribution patternof species richness between water-associated habitats against non water-associated habitats. Weconcluded that bird diversity from the Chillón valley is influenced by altitude and this pattern isrepresentative of the western slope of central Peru.